Is a convivial synthetic biology possible? - Matthew J. Tarnowski; Mario Pansera (Journal of Responsible Innovation)
Synthetic biology predominantly follows a market-driven approach, both within the private sector and academia. We present a research journey undertaken by a synthetic biologist who received guidance from responsible innovation scholars, reflecting on the wider effects of synthetic biology technologies. The outcome is a re-evaluation of synthetic biology through the lens of ‘conviviality’, a concept introduced by Ivan Illich to designate a modern society of responsibly limited tools, where individual freedom is realised through personal interdependence. We find that in its current form, synthetic biology is not convivial since it relies on centralisation, monopolies and technologies which have the capacity to negatively affect the biosphere and its inhabitants. We argue that a broader conception of biotechnology, beyond genetics, is needed to conceive convivial biotechnologies. In our research journey we explore a range of approaches for responsible biotechnology innovation, which includes open-source, commons-based, decentralised organisations, and post-growth models.